Does College Education Make Women Less Likely to Marry? Evidence from the Chinese Higher education Expansion - Bin Huang; Massimiliano Tani; Lei Xu; Yu Zhu (Institute of Labor Economics (IZA), 2025)
We study the impact of higher education (HE) on marriage incidence in China using the 2017 China Household Finance Survey. Taking advantage of the dramatic HE expansion starting in 1999, we explore the effect of education on marriage outcomes by instrumenting years of schooling using the interaction of childhood urban hukou status and a set of time dummy and trend variables capturing the exposure to the expansion. Contrary to conventional wisdom, the 2SLS results suggest that increased education induced by the HE expansion leads to higher marriage rates. These positive effects tend to be larger for women living in coastal areas or larger cities. The estimates are robust to alternative specifications, age range, the age cut-offs for childhood hukou status and controls for birth cohort-city specific sex ratios. Our findings imply that the strong negative relationship observed between college education and marriage outcomes for women is likely driven by educational assortative mating due to persistent gender norms in favour of status hypergamy, which prevents the Chinese marriage market from adjusting to the reversed gender gap in HE post-expansion.
Keywords: I23; J12; 330; educational assortative mating; 2SLS; marriage market outcomes; higher education expansion; China